2019
DOI: 10.1128/jb.00370-19
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Warfare: Interaction of Pneumococcal Bacteriophages with Their Host

Abstract: Virus-host interactions are regulated by complex coevolutionary dynamics. In Streptococcus pneumoniae, phase-variable type I restriction-modification (R-M) systems are part of the core genome. We hypothesized that the ability of the R-M systems to switch between six target DNA specificities also has a key role in preventing the spread of bacteriophages. Using the streptococcal temperate bacteriophage SpSL1, we show that the variants of both the SpnIII and SpnIV R-M systems are able to restrict invading bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…This could imply that there is less selective pressure to generate phenotypic diversity in these organisms as they exist in a more predicatable environment and use the conventional "sense and respond" gene regulation paradigm of adaptability, that is, these organisms contain many more two-component sensor-regulator pairs than small genome pathogens that contain multiphase-variable methyltransferases. 66 Variation in methyltransferases has also be shown to protect against incoming foreign DNA/phage in numerous diverse bacterial species such as Lactococcus lactis 24 Enterococcus faecium 67 Mycoplasma pulmonis 28 and H. influenzae. Increased phenotypic diversity is an obvious advantage of phasevarions, particularly in small genome, host-adapted pathogens; perhaps the increased variablity generated by phasevarions provides a number of additional advantages during adaptation to changing environmental conditions that these organisms may encounter, or that cannot be sensed by conventional means.…”
Section: Discussionmentioning
confidence: 99%
“…This could imply that there is less selective pressure to generate phenotypic diversity in these organisms as they exist in a more predicatable environment and use the conventional "sense and respond" gene regulation paradigm of adaptability, that is, these organisms contain many more two-component sensor-regulator pairs than small genome pathogens that contain multiphase-variable methyltransferases. 66 Variation in methyltransferases has also be shown to protect against incoming foreign DNA/phage in numerous diverse bacterial species such as Lactococcus lactis 24 Enterococcus faecium 67 Mycoplasma pulmonis 28 and H. influenzae. Increased phenotypic diversity is an obvious advantage of phasevarions, particularly in small genome, host-adapted pathogens; perhaps the increased variablity generated by phasevarions provides a number of additional advantages during adaptation to changing environmental conditions that these organisms may encounter, or that cannot be sensed by conventional means.…”
Section: Discussionmentioning
confidence: 99%
“…An additional consideration is that the human nasopharynx is a source of phages capable of infecting S. pneumoniae as recently demonstrated by Furi et al 18 . This work also shows that the number of SpnIII sites present in a phage genome will determine how likely it is to be successfully restricted by the infected cell, and therefore determine the likelihood of that cell's survival.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences recognised by these different TRD combinations are referred to as A-F 7,16 . These www.nature.com/scientificreports www.nature.com/scientificreports/ differential methylation patterns have previously been shown to impact the ability of S. pneumoniae to take up DNA following transfection and transformation 7,8,17,18 , but even more importantly to have epigenetic effects influencing the ability of SpnIII variants to colonise the murine nasopharynx and blood stream 7 and on colony opacity variation [7][8][9] . However, no difference in the prevalence of active spnIII hsdS genes was found when comparing paired isolates from human cerebrospinal fluid or blood 19 .…”
mentioning
confidence: 96%
“…In 2019, Turkington et al showed that experimental compartmentalisation of stochastic switching states in a meta‐population can act to introduce herd immunity to phage infection (Figure d) (Turkington, Morozov, Clokie & Bayliss, ). In a similar example, Furi and Colleagues () found that infection of S. pneumoniae populations by a phage was dependent on the methylation state of the phage, the number of methylation sites in the phage genome and the predominant phase state of the bacterial SpnIII system that can switch between six differing states. An under‐explored aspect of both of these scenarios was that pre‐exposure to phage or other selective pressures had the potential to influence the meta‐population structure.…”
Section: Application Of Mathematical Models To Understanding How Lh Cmentioning
confidence: 99%